Putative SARS-CoV-2 M(pro) Inhibitors from an In-House Library of Natural and Nature-Inspired Products: A Virtual Screening and Molecular Docking Study - Mazzini, Stefania (Molecules, 2020)
A novel coronavirus (severe acute respiratory syndrome coronavirus 2, SARS-CoV-2) has been the cause of a recent global pandemic. The highly contagious nature of this life-threatening virus makes it imperative to find therapies to counteract its diffusion. The main protease (M(pro)) of SARS-CoV-2 is a promising drug target due to its indispensable role in viral replication inside the host. Using a combined two-steps approach of virtual screening and molecular docking techniques, we have screened an in-house collection of small molecules, mainly composed of natural and nature-inspired compounds. The molecules were selected with high structural diversity to cover a wide range of chemical space into the enzyme pockets. Virtual screening experiments were performed using the blind docking mode of the AutoDock Vina software. Virtual screening allowed the selection of structurally heterogeneous compounds capable of interacting effectively with the enzymatic site of SARS-CoV-2 M(pro). The compounds showing the best interaction with the protein were re-scored by molecular docking as implemented in AutoDock, while the stability of the complexes was tested by molecular dynamics. The most promising candidates revealed a good ability to fit into the protein binding pocket and to reach the catalytic dyad. There is a high probability that at least one of the selected scaffolds could be promising for further research